Pengaturan Perizinan Berusaha Pemerintah Kota Batam Sebelum dan Sesudah UU Cipta Kerja: Batam City Government Business Licensing Arrangements Before and After the Job Creation Law - Shinta Pangesti (Warkat, 2021)
In the new normal era, the impact of the Covid-19 pandemic is still very much felt, especially in the economic sector. In line with the investment recovery agenda in Indonesia, the Government has taken steps to simplify regulations, one of which is in managing business permits as mandated by the Job Creation Law and its implementing regulations. In order to obtain a comparison of business licensing arrangements in Batam City before and after the enactment of the Job Creation Law, the author examines how business licensing arrangements in Batam City are reviewed from the Mayor of Batam No. 40/2020 jo. Batam Mayor Regulation no. 56/2020 jis. Job Creation Law jo. PP No. 5/2021 jo. PP No. 6/2021? This research is normative legal research using primary, secondary and non-legal legal materials. Because the new Batam mayoral regulations regarding business licensing have not yet been established, the existing old provisions remain in effect as long as they have not been revoked. Adjustment of mayor regulations to the provisions in PP no. 5/2021 jo. PP No. 6/2021 needs to be implemented immediately to realize legal certainty in business licensing.